Quantitative determination of total flavonoids in Glycyrrhiza Glabra L. herbs - O. A. Belova; V. A. Kurkin; M. V. Egorov (Фармация и фармакология (Пятигорск), 2023)
Licorice herb (Glycyrrhiza glabra L.) is a promising herbal raw material, which can be comprehensively used to develop drugs with an anti-inflammatory action.The aim of the article was to development a quantitative determination method of total flavonoids in Glycyrrhiza glabra L. herbs.Materials and methods. The subjects of research were 5 samples of licorice herb harvested in summer in various places of growing and cultivation. Pinostrobin was used as a standard sample. The registration of the electronic spectra was carried out with a spectrophotometer (Analytik Jena AG, Germany) by differential spectrophotometry, 96% ethanol was used as a solvent.Results. The methods for quantitative determination of total flavonoids in Glycyrrhiza glabra L. was carried out at an analytical wavelength of 310 nm equivalent to pinocembrin. The optimum parameters for the extraction of total flavonoids from Glycyrrhiza glabra L. were as follows: the extractant – 90% ethanol; the «raw material-extractant» ratio was 1:50; the extraction time was 60 min; the degree of atomization was 2 mm. The content of total flavonoids for the Glyccyrhiza glabra L. herb has been determined, it varies from 0.39±0.002 to 3.41±0.015% with the humidity of the vegetative raw material from 9.97±0.003 to 10.03±0.003% depending on the place of the vegetation, cultivation and year of the raw material collection. The error of the single determination with a 95% confidence level was ±0.73%.Conclusion. The developed methods for the quantitative determination of total flavonoids in Glycyrrhiza glabra L. herbs can be used to solve the issues of standardization of these medicinal plant raw materials.